Complex of ultrasound techniques in diagnosis of nodular thyroid pathology - A. V. Pomortsev; O. V. Astafeva; Y. S. Degtiareova; O. I. Achrarova (Кубанский научный медицинский вестник, 2014)
The objectives of this study is evaluation of the role of elastography of shear wave in addition to color Doppler ultrasound in differential diagnosis of the focal thyroid pathology. For this purpose 134 patients with different nodal pathology of thyroid gland were examined before surgery. The acquired elastography datasets were comparable to the morphologycal analysis at the thyroid gland biopsy. We've concluded that the elastography of shear wave with color Doppler ultrasound provide a more reliable and valid assessment of the thyroid nodule, than both 2D ultrasound imaging and Color Doppler. This technique can aid in the diagnosis of thyroid cancer more early.